Finance of foreign trade and foreign exchange - Whiting, D. P. (Plymouth : Macdonald and Evans, 1976)
This text is suitable for HND or degree students studying banking and finance .Iit can also come handy for the import/export manager in a firm
Rev. ed. published as: Finance of international trade. 4th ed. 1981.
Includes index.
ijb, 14/01/2019
Loans
Keywords: Foreign exchange; International finance